2019
DOI: 10.5935/abc.20190142
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels in Peripheral Artery Disease Patients

Abstract: BackgroundIncreases in daily physical activity levels is recommended for patients with peripheral artery disease (PAD). However, despite this recommendation, little is known about the physical activity patterns of PAD patients.ObjectiveTo describe the physical activity patterns of patients with symptomatic peripheral artery (PAD) disease.MethodsThis cross-sectional study included 174 PAD patients with intermittent claudication symptoms. Patients were submitted to clinical, hemodynamic and functional evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 32 publications
3
41
0
5
Order By: Relevance
“…' DISCUSSION IC is the clinical manifestation of PAD that typically hinders patients' usual activities by decreasing their ability to walk daily (15,16) and consequently reduce their quality of life (17). The initial treatment of IC is often clinical because, with conservative treatment, most patients experience improvement or stability in their clinical manifestations combined with a low risk of amputation.…”
Section: ' Resultsmentioning
confidence: 99%
“…' DISCUSSION IC is the clinical manifestation of PAD that typically hinders patients' usual activities by decreasing their ability to walk daily (15,16) and consequently reduce their quality of life (17). The initial treatment of IC is often clinical because, with conservative treatment, most patients experience improvement or stability in their clinical manifestations combined with a low risk of amputation.…”
Section: ' Resultsmentioning
confidence: 99%
“…Women were less likely to exceed VT during the 6-minute walk test than men, indicating that ground walking is performed at a lower relative intensity by women than by men. This is surprising given previous studies 27,28 have shown that women with symptomatic PAD have lower walking capacity, 29,30 are less physically active 29,30 and report more barriers to practicing physical activity compared to men. 31 In addition, women present more adverse calf muscle characteristics and lower VO 2 peak than men.…”
Section: Discussionmentioning
confidence: 83%
“…As mulheres tiveram menos probabilidade de exceder o LV durante o teste de caminhada de 6 minutos do que os homens, indicando realização em menor intensidade relativa pelas mulheres do que pelos homens. Isso é surpreendente dado que estudos anteriores 27 , 28 demonstraram que mulheres com DAP sintomática apresentam menor capacidade de deambulação, 29 , 30 são menos ativas fisicamente 29 , 30 e relatam mais obstáculos à prática de atividade física em comparação aos homens. 31 Além disso, as mulheres têm mais características adversas nos músculos da panturrilha e menor pico de VO 2 que os homens.…”
Section: Discussionunclassified
“…Dari penelitian tersebut disebutkan bahwa ABI yang rendah berhubungan dengan IMT yang tinggi (Bąk, et al, 2016). Studi lainnya menunjukkan bahwa kebiasaan responden dengan aktifitas yang sedenter sering ditemukan pada pasien PAD di Brazil (Gerage, et al, 2019). Penelitian yang mengkaji hubungan IMT dengan ABI pada etnis Jawa yang merupakan etnis terbesar di Indonesia belum pernah dilaporkan.…”
Section: Pendahuluanunclassified